Spirit Zakat untuk Kemandirian Umat: Ekplorasi Program Pengelolaan Zakat yang Efektif: Spirit of Zakat for Community Independence: Exploration of Effective Zakat Management Program - Azwar, Azwar (Litera Academica Publishing, 2024)
Zakat, as one of the pillars of Islam, plays an important role in improving the welfare of the community, particularly in creating economic independence for mustahik (zakat recipients). Although zakat is generally used to meet the basic needs of mustahik, this consumptive approach is considered insufficient for sustainably empowering mustahik. Therefore, this study aims to identify and analyze zakat management programs that can support economic empowerment of the community, with a focus on creating independence for mustahik. This research uses a qualitative approach with a descriptive-analytical design. The results show that effective zakat management programs include the establishment of microenterprises, skills training, provision of business capital, mentoring in small business management, and educational assistance. The recommendations from this study emphasize the importance of applying transparency and accountability principles in zakat management to ensure that zakat is distributed to the right recipients and provides maximum benefits for mustahik, while also encouraging the transformation of mustahik into muzakki (zakat payers).